Analisis Alur Mundur pada Novel Perempuan Patah Hati Yang Kembali Menemukan Cinta Melalui Mimpi Karya Eka Kurniawan - Katharina Woli Namang; Fathia Aulia Muthmainna (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This article identifies and describes "The Backward Flow Analysis In the Short Stories of Women, Broken Hearts of Whom Re-Had discovered the Quantitative Love Through Dreams of Eka Kurniawan, the purpose of this research paragraph is to provide information and describe the back dreams contained in this research method. The short story collection is Ginc This Red, Darling, Broken Heart Women Again Finding Love through Dreams, Making Happy A Elephant, Stone Story, Every Dog Can Be Happy, Burning Fire, and keep Parrot Lessons